2014
DOI: 10.1155/2014/962764
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prophylactic Polishing Pastes on Surface Roughness of Indirect Restorative Materials

Abstract: The purpose of this study was to evaluate the influence of prophylactic polishing pastes (PPP; Detartrine (DT), Topex (TP)) on surface roughness (R a) of indirect composites (IRC; Tescera (TES), Gradia (GRD), and Estenia C&B (EST)), a glass ceramic (Empress 2 layering (E2)), and a leucite reinforced glass ceramic (Empress Esthetic (EE)) with two different (glazed (G); polished (P)) surface preparations. A total of 90 IRC and 120 ceramic discs, 8 mm in diameter and 2 mm thick, were prepared. E2 and EE specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Thus, when the filler particles are harder than the surrounding resin matrix, the simulated toothbrushing abrades the matrix easily, leading to increased surface roughness and gloss. On the other hand, authors have reported that a homogenous mixture of fillers in the material results in a consistent form of abrasion under toothbrushing; thus, the surface maintains its gloss and shows lower surface roughness [26]. In the author's opinion, this is the possible reason for the overall significant influence of roughness and the low influence on gloss due to toothbrush abrasion, as observed in the present study [27].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, when the filler particles are harder than the surrounding resin matrix, the simulated toothbrushing abrades the matrix easily, leading to increased surface roughness and gloss. On the other hand, authors have reported that a homogenous mixture of fillers in the material results in a consistent form of abrasion under toothbrushing; thus, the surface maintains its gloss and shows lower surface roughness [26]. In the author's opinion, this is the possible reason for the overall significant influence of roughness and the low influence on gloss due to toothbrush abrasion, as observed in the present study [27].…”
Section: Discussionsupporting
confidence: 58%
“…The inorganic content was significantly different in all the polymer-infiltrated ceramic, with Vita Enamic greater than Lava Ultimate, and CU having higher inorganic content than Shofu Block HC. Studies have shown controversial outcomes on the correlation of filler content and surface roughness; however, filler size, filler form, and polymeric matrix played an essential role in influencing the surface quality of the polymer-infiltrated ceramics [25,26]. Moreover, the loss of gloss is influenced by silanization of fillers, size, form, and resin matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ceramics mechanically polished for just 30 s showed no difference between their initial surface conditions ( 25 ). Can et al state that mechanical polishing affects glaze-treated ceramic surfaces ( 34 ). In our study, we applied mechanical surface treatment via a polishing kit, and each procedure was applied for at least 60 s.…”
Section: Discussionmentioning
confidence: 99%
“…PP pastes cause three-body wear by serving a third body between the restoration and polishing instrument. The resin matrix loss between filler particles and the subsequent debonding of filler particles result in an even rougher surface [23]. Accordingly, the surface roughness values of FC, IC, and CC specimens were significantly increased by RP.…”
Section: Discussionmentioning
confidence: 99%